A double-float structured triboelectric nanogenerator for wave hydrological monitoring. (December 2022) - Wang, Xiaoning; Hu, Yili; Li, Jianping; Ma, Jijie; Wan, Nen; Wen, Jianming; Cheng, Tinghai
Graphical abstract: Highlights: A·new idea·of a double-float structured triboelectric nanogenerator (DF-TENG) for Wave hydrological monitoring is firstly proposed. The DF-TENG with simple but durable double-float structure can monitor the motion of waves effectively: wave height, wave motion frequency and period, wave vertical speed. A frequency-domain parameter N s is proposed which shows a great robustness under the influence of enviromental factors (humidity, temperature and wind force). Abstract: Triboelectric nanogenerator (TENG) is one technique for real-time monitoring of wave hydrology. However, the influence of environmental factors is a key problem for the practical application of TENGs. In this study, a TENG with a simple but durable double-float structure (DF-TENG) for wave hydrological monitoring is proposed and analyzed. Different with traditional TENGs, the frequency-domain parameter N s (number of sub-signals) is utilized. Experiments indicate that the designed DF-TENG is effective to measure the wave hydrological information (wave height, motion frequency, motion period and vertical speed) with great robustness even under the influence of environmental factors (humidity, temperature and wind force). In the case that wave height increases gradually from H r  = 35 mm to H r  = 145 mm, N s raises up from N s  = 4.5 to N s  = 20. A linear relationship between N s and H r is obtained as N s  = 0.1346 H r − 0.2821, with a perfect correlation of R 2  = 0.99. More importantly, the proposed N s shows great robustness and the fluctuation of it is almost zero even under different environmental factors. This study confirms the feasibility of the DF-TENG for continuous monitoring of wave hydrology, which is meaningful for the real application of TENGs in the future.